Are anthropometric characteristics powerful markers to predict the Cooper Run Test? Actual Caucasian data - Gianluca Azzali; Massimo Bellato; Matteo Giuriato; Vittoria Carnevale Pellino; Matteo Vandoni; Gabriele Ceccarelli; Nicola Lovecchio (PeerJ, 2023)
Background Cardiorespiratory fitness (CRF) is a powerful marker of cardiovascular health, especially in youth. Several field tests can provide accurate measurement of CRF, the Cooper Run Test (CRT) is generally preferred by physical education (PE) teachers and trainers. The CRT performance in adolescents has been compared to reference distance values, gender and age but the differences among the anthropometric characteristics of youth has not been evaluated. For these reasons, the aim of this study was to develop reference standards for CRT and evaluate possible correlations between biometric measurements and athletic performance. Methods This cross-sectional study involved a total of 9,477 children (4,615 girls) aged 11–14 years, freely recruited from North Italian middle schools. Mass, height and CRT performances were assessed in the morning during PE classes as scheduled (mornings-Monday to Friday). The anthropometric measures were collected at least 20 min before the CRT run test. Results We found a better CRT result in boys (p < 0.001), however a smaller SD in girls suggested a more homogeneous aerobic performance for girls (i.e., 371.12 m vs 282.00 m). In addition, the Shapiro-Wilk test showed a low p-value (p < 0.001) but the effect size (0.031 for boys and 0.022 for girls) was small enough that the correction on this parameter allows a practical assumption of normality for the distributions. A visual homoskedastic distribution in both sexes is evident for both body mass index (BMI), mass and VO2 peak with respect to CRT results. In addition, there were low linear correlation coefficients for both BMI, mass and VO2 peak compared to the CRT results, with a R2 < 0.5 for every covariate. The only visual heteroskedastic distribution was observed in regression between distance in CRT and age at peak high velocity. Conclusions Our findings suggested that anthropometric characteristics are not powerful markers to predict Cooper Run Test results in a well-mixed, unpolarized and unbiased pool of middle school boys and girls. PE teachers and trainers should prefer endurance tests over the use of indirect formulas to predict performance.